2015
DOI: 10.4269/ajtmh.15-0309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nested Polymerase Chain Reaction and Real-Time Polymerase Chain Reaction with Parasitological Methods for Detection of Strongyloides stercoralis in Human Fecal Samples

Abstract: Abstract. This study was performed to evaluate nested polymerase chain reaction (PCR) and real-time PCR methods for detection of Strongyloides stercoralis in fecal samples compared with parasitological methods. A total of 466 stool samples were examined by conventional parasitological methods (formalin ether concentration [FEC] and agar plate culture [APC]). DNA was extracted using an in-house method, and mitochondrial cytochrome c oxidase subunit 1 and 18S ribosomal genes were amplified by nested PCR and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 25 publications
2
69
1
2
Order By: Relevance
“…However, this test also can give a positive result in the setting of hookworm infection and can contribute to perceived false negatives and an overall low sensitivity seen in some studies using qPCR 26,61,62. However, in many epidemiologic surveys, qPCR has typically increased overall diagnostic yield by 2- to 8-fold when compared with a variety of microscopic techniques 12,19,27,45,51,63,73. Unlike the other STH, however, the quantification of larvae in the stool has not been shown to predict the adult worm burden, and so qPCR would not be used as a reflection of adult worm burden in a clinical setting.…”
Section: Qpcr In the Detection Of Each Of The Major Sthmentioning
confidence: 99%
“…However, this test also can give a positive result in the setting of hookworm infection and can contribute to perceived false negatives and an overall low sensitivity seen in some studies using qPCR 26,61,62. However, in many epidemiologic surveys, qPCR has typically increased overall diagnostic yield by 2- to 8-fold when compared with a variety of microscopic techniques 12,19,27,45,51,63,73. Unlike the other STH, however, the quantification of larvae in the stool has not been shown to predict the adult worm burden, and so qPCR would not be used as a reflection of adult worm burden in a clinical setting.…”
Section: Qpcr In the Detection Of Each Of The Major Sthmentioning
confidence: 99%
“…No PCR studies have reported false positive results when analytical specificity has been tested using DNA extracted from bacteria, viruses, fungi, protozoa, and other helminths 19,23,24,27,29,30 . Studies have also assessed the specificity of the PCR products by sequence analysis, with all finding 100% sequence homology with the target sequence of S. stercoralis.…”
Section: Pcrmentioning
confidence: 99%
“…Studies have also assessed the specificity of the PCR products by sequence analysis, with all finding 100% sequence homology with the target sequence of S. stercoralis. 24,25,27,29 . Sitta et al found a number of false positives, using published genus and species-specific primers, based on non-target sized bands on gel electrophoresis 19,25 .…”
Section: Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Similar approach was adopted to detect S. stercoralis in human feces using real-time PCR with species-specific target genes, such as cytochrome c oxidase, 18S rRNA, and 5.8S rRNA. [62][63][64][65][66] The real-time PCR was 100% specific but failed to enhance the sensitivity to detect strongyloidiasis compared to parasite concentration methods. 67 The major disadvantage of DNAbased detection is that the amount of parasite-specific DNA in the feces is variable because of sporadic larval release, and in asymptomatic patients with very low levels of larval output, the test is unlikely to achieve a higher sensitivity unless repeated stool samples are tested.…”
Section: Diagnostic Advancesmentioning
confidence: 99%